Evaluation of second-international-standard-based reagent kit Lumipulse Presto HBsAb-III - KIMURA, Chihiro; OKUBO, Manabu; KOHGUCHI, Yutaka; UESUGI, Satoe; MAEDA, Hitomi; TOHYAMA, Kaoru; FURUKAWA, Satoko (Japanese Journal of Medical Technology, 2021)
The hepatitis B virus (HBV) surface antibody (HBsAb) is used for the diagnosis of HBV infections and is a marker that appears after vaccination. We evaluated the second-international-standard-based reagent kit for anti-hepatitis B surface antigen (anti-HBs) immunoglobulin (NIBSCcode: 07/164), Lumipulse Presto HBsAb-III (Lumipulse 2nd reagent) and compared it with Lumipulse Presto HBsAb-N (Lumipulse 1st reagent). Within-run and between-run reproducibility precisions were 1.6–3.0% and 1.7–3.8%, respectively. The obtained diluted linearity and lower limit of detection were 1,000.0 and 0.9 mIU/mL, respectively. The correlation coefficient (r) between Lumipulse 2nd reagent and Lumipulse 1st reagent was 0.997. The cutoff value (10.0 mIU/mL) for the concordance rate of the Lumipulse 2nd and 1st reagents was 100%. The basal performance of the Lumipulse 2nd reagent was satisfactory, and it could be used for measurement with high sensitivity.